Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Skincare Skintific - Ardi Goeliling; Ni Nyoman Devi; Ariyani Goeliling; Romansyah Sahabuddin; Arya Pering Arimbawa; Fatmawati A Rahman; A Fadel Muhammad (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
The purpose of this research is to explore the impact of price and product quality on purchase decisions, focusing on the skincare product Skintific. This research utilizes a descriptive quantitative approach. The data used consists of primary data obtained through surveys using questionnaires given to respondents, as well as secondary data collected through internet searches and references from previous studies relevant to this research topic. The subjects of this research are female university students in Makassar who have purchased and used Skintific skincare products. Non-probability sampling with a purposive sampling approach was employed to select 100 participants for this study. The findings of this research indicate that both price and product quality, separately and together, have a significant influence on the purchase decision of Skintific skincare products.